VD_FINDINFO HC / 2021 / 301 vom 31. Mai 2021 - VD Tribunal cantonal (2021)
OBLIGATION D'ENTRETIEN, MAJORITÉ{ÂGE}, ENFANT, PRÉVOYANCE PROFESSIONNELLE, PARTAGESENS GÉNÉRAL, DIVORCE | 122 CC, 124 CC, 124b al. 2 CC, 276a al. 1 CC, 279 CC, 285 CC